Chronic hypoxia prolongs postoperative mechanical ventilation and reduces the left atrial pressure threshold in children with tetralogy of Fallot - Huang, Jiangshan; Ding, Jie; Wu, Xie; Jia, Yuan; Liu, Qiao; Yuan, Su; Yan, Fuxia (Frontiers in Pediatrics, 2023)
Background: Chronic hypoxia induces pulmonary microvascular endothelial dysfunction. The left atrial pressure (LAP) represents the hydrostatic pressure of the pulmonary microcirculation. The conjunction of the LAP and any abnormal pulmonary microvascular endothelial barrier function will have an impact on pulmonary exudation, resulting in prolonged mechanical ventilation. This study aimed to investigate the tolerance threshold of the pulmonary microcirculation to LAP in children with tetralogy of Fallot (TOF), to avoid prolonged mechanical ventilation after surgery. Methods: This retrospective study included 297 Chinese patients who underwent TOF correction at Fuwai Hospital. Patients were categorized according to their preoperative oxygen saturation (SpO2) level. One-to-one propensity score matching (PSM) revealed a total of 126 participants in the SpO2<90% and SpO2≥90% groups. Between-group comparisons were conducted to verify the correlation between hypoxia and prolonged mechanical ventilation. A subgroup analysis was performed to reveal the significant role of postoperative LAP stewardship on prolonged mechanical ventilation. Results: Failure to extubate within first 48 hours (23.81% vs. 9.52%, P = 0.031) and prolonged mechanical ventilation (26.98% vs. 11.11%, P = 0.023) were more commonly observed in children with preoperative SpO2 < 90%. The incidence of prolonged mechanical ventilation consistently increased with LAP in both the SpO2 < 90% and SpO2 ≥ 90% groups, although LAP was still within the normal range (6-12 mmHg). Children in chronic hypoxic conditions tolerated lower LAP well. The tolerance threshold for postoperative LAP in children diagnosed with TOF under chronic hypoxic conditions was identified as 7mmHg. Conclusions: Children in a chronic hypoxic state may suffer from a high incidence of prolonged mechanical ventilation after surgical correction of TOF and may not tolerate higher postoperative LAP. To improve pulmonary prognosis, it is better to control and maintain the postoperative LAP at a lower state (≤7mmHg) in children with chronic hypoxia.